FUNDAMENTOS PEDAGÓGICOS PRESENTES NAS RELIGIÕES DE MATRIZ AFRICANA - Santos, Ademir Barros dos (Sankofa (São Paulo), 2021)
With a focus on the resilience of African pedagogical practices, which resist in the religious environments of this matrix present in Brazil, despite the intense and violent opposition to which its components, for more than half a millennium, have been exposed, this article, which is based on , previous study embodied in a master's dissertation, seeks to present the elements that, despite everything, support, consolidate and perpetuate original knowledge, although not using writing, an officially constituted master or any other element of fixation present in school education practiced in the Western European model. As a result, the article points to the presence of powerful pedagogical and cultural instruments that, although they seem informal, relegate and face the “banking” teaching so criticized by Freire, because they are based on philosophical, theological and anthropological foundations active in African culture here, presenting valid and effective pedagogical alternatives that, even in the face of the blatant ex-explicit violence present in the hostile society with which they live, resist and perpetuate themselves, almost incredulously.